Pemberdayaan Masyarakat Dalam Penanggulangan Air Limbah Rumah Tangga Menjadi Pupuk Kompos Dengan Sistem Biopori Di Desa Jembatan Kembar Timur Kabupaten Lombok Barat - Hasyim; Rohani; Karyawan, I Dewa Made Alit; Negara, I Dewa Gede Jaya; Yasa, I Wayan; Saidah, Humairo; Mahendra, Made; Suteja, I Wayan; Salehudin; Sideman, IAO Suwati (Universitas Mataram, 2024)
The legal age of marriage in Indonesia is a man and woman who have reached the age of 19 as stated in Law Number 16 of 2019 on the amendment of Law Number 1 of 1974 concerning marriage in Indonesia. Marriage under the age of 19 is called early marriage, which is known as the